Legal Regulation of Digital Real Rights in Cyberspace: A Comparative Study - Youssef, Kadhim; Hassan, Majid (Journal of Legal Sciences, 2026)
This research addresses the problem of the legal regulation of real rights over virtual assets in the absence of explicit legislative provisions in many legal systems. The study aims to adapt the legal nature of digital assets and cryptocurrencies and to clarify their suitability to be the subject of principal and accessory real rights. The study adopts a comparative analytical approach among Iraqi, Egyptian, French, and English civil laws, while reviewing the opinions of jurists and recent judicial applications. The study concludes that virtual assets are intangible assets that accept ownership and constructive possession, and recommends the necessity of urgent legislative intervention to regulate the provisions of their acquisition, transfer, and civil protection, in a manner that keeps pace with technological development and achieves stability in digital transactions.